Physical performance and bioelectrical impedance vector analysis of female track and field athletes according to the follicular phase of the menstrual cycle - Mascherini, G.; Serafini, S.; Bianchi, E.; Izzicupo, P.; Micheli, M. L. (Sport Sciences for Health, 2025)
Purpose The menstrual cycle (MC) and body composition are key biological variables in the study of female sports performance. This study aims to evaluate changes in body composition and performance during the follicular phase of the MC and verify any possible relationship between these changes.